Material Fantasies Expectations of the Western Consumer World among the East Germans - Veenis, Milena (Technology and European History Series, 2012)
This study of East German fantasies of material abundance across the border, both before and after the fall of communism, shows the close and intricate relation between ideology and fantasy in upholding social life. In 1989, news broadcasts all over the world were dominated for weeks by images of East Germans crossing the Berlin Wall to West Germany. The images, representing the fall of communism and the democratic will of the people, also showed East Germans' excitement at finally being able to enter the western consumer paradise. But what exactly had they expected to find on the other side of the Wall? Why did they shed tears of joy when for the first time in their lives, they stepped inside West German shops? And why were they prepared to pay more than 10 percent of their average monthly wage for a pineapple? - http://www.aup.nl/do.php?a=process_visitor_download&editorial_id=3477 - >Download an excerpt. Drawing on fifteen months of research in the fast-changing post-communist East Germany, Veenis unravels the perennial truths about the interrelationships of fantasies of material wealth, personal fulfillment and social cohesion. She argues persuasively that the far-fetched socialist and capitalist promises of consumption as the road to ultimate well-being, the partial realization and partial corruption thereof, the implicit social and psychological interests underlying the politicized promises in both countries form the breeding ground for the development of materialist, cargo-cult-like fantasies, in which material well-being came to be seen as the place of - fulfillment and ultimate arrival - . Material Fantasies is published in the Technology and European History series. The series seeks to present scholarship about the role of technology in European history in the nineteenth and twentieth centuries. For more information on the network, the Foundation for the History of Technology and the series, see: - http://www.tensionsofeurope.eu - >www.tensionsofeurope.eu.